Revisiting The Critical Edition of the Qur'an: Historical Perspectives and Contemporary Challenges - Farida, Khusna (UIN Sunan Kalijaga Yogyakarta, 2024)
The concept of a critical edition of the Qur'an resurfaced following earlier attempts by western scholars such as Bergstresser (w. 1351 AH/1933 AD), Jeffery (w. 1378 AH/1959 AD), and Pretzl (w. 1360 AH/1941 AD), who were supported by Fischer (w. 1369 H/1949 M), Baumstark (w. 1368 AH/1948 AD), Ritter (w. 1391 AH/1971 AD), and Kahle (w. 1384 AH/1964 AD). In a conference at the University of Notre Dame in April 2005, Gabriel Said Reynolds proposed “The New Reading of the Qur`an” for updating textual reseacrh on the Qur`an, after various manuscripts were discovered as research material for the Qur`an. Additionally, among those who contributed to the conceptualization of the Critical Edition of the Qur'ān is Taufik Adnan Amal, a Muslim scholar. This qualitative-historical research, I examine the ideas of the Bergstresser, Jeffery, dan Pretzl’s version of the Critical Edition of the Qur`a and Taufik Adnan Amal’s version to find out whether both of them are same or different. As well, this study aims to answer the possibility of the existence of a contemporary Critical Edition of the Qur'an as implied by both of them. Even though they use the same term, their Critical Edition of Quran do not only have similarities, but also have differences. As for the possibility of using the ikhtiyâr technique at the present time to produce a Critical Edition for the Qur`an, many factors must be considered and should comply with the conditions that apply. One of them, if it is still possible, there are maqbûl readings outside the ten. The reciters who perform ikhtiyâr must also have a sanadreaching to Rasulullah saw.